The Analysis Study Effect of Intermittent Fasting on Female Reproductive Hormones and Menstrual Cycle: A Comprehensive Systematic Review - Tuswandi Ahmad Waly; Bayu Setyo Nugroho (International Medical Journal Corp. Ltd, 2025)
Background: Intermittent fasting (IF) has surged in popularity as a dietary approach for weight management and metabolic health, yet its effects on female reproductive hormones and menstrual cycle regulation remain an area of growing scientific inquiry. This systematic review aims to evaluate the influence of IF on female reproductive hormones and menstrual cycle. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: IF presents both potential benefits and risks for female reproductive health. While it may aid in weight loss, improve insulin sensitivity, and reduce inflammation, concerns remain about its effects on hormonal circadian rhythms and reproductive function. Individualized approaches that consider metabolic status, hormonal health, and lifestyle factors are essential for optimizing the benefits of IF while minimizing potential adverse effects on female reproductive hormones and menstrual cycles.